The Failure of Normative Ethics to Counter Disinformation in the Campus Ecosystem: A Case Study of Students at Jakarta State University - Dinda Sasikirana; Keyla Kanigara; Muhammad Raihan Alhadi; Siti Hajar; Abdul Fadhil (Institut Agama Islam Persis Bandung, 2025)
The rapid proliferation of cyberspace has precipitated an epistemological crisis that demands analytical and ethical competencies beyond instrumental digital skills. This article deconstructs the perceptions of university students regarding the application of akhlakul karimah (noble character) as a foundational framework for critical social media literacy. Employing a sequential explanatory mixed-methods design, this study utilized a preliminary quantitative survey (N=45) to map normative claims, followed by in-depth qualitative interviews (N=7) with informants representing extreme behavioral anomalies. Findings reveal a profound epistemological paradox: while students demonstrate high conceptual awareness of digital politeness, they fundamentally reduce akhlakul karimah to passive normative compliance and conflict-avoidance strategies. Consequently, these ethical values fail to translate into critical evaluation skills, such as empirical source verification (tabayyun) and logical autonomy amidst disinformation. Further analysis indicates that this cognitive dissonance is exacerbated by confirmation bias, the Dunning-Kruger effect, and sociological repression within peer echo chambers. This study concludes that character education in higher learning institutions requires a radical pedagogical paradigm shift. Akhlakul karimah must be reconstructed from a passive metric of piety into an emancipatory analytical methodology, integrating scientific skepticism to fortify students' rational autonomy against the hegemony of algorithmic manipulation